Outbreak of Extended Spectrum Beta Lactamase Producing Klebsiella Species Causing Neonatal Sepsis at Patan Hospital in Nepal - Amatya, Puja; Joshi, Suchita; Shrestha, Shrijana (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Klebsiella sepsis is the most important nosocomial infection in neonates. The objectives of this study were to review an outbreak in a neonatal unit caused by Klebsiella species, to identify the source of the infections, and to identify infection control measures for eradication and prevention of these infections. Methods: The case notes and investigation reports of all sepsis cases admitted in neonatal units of Patan hospital from July to December 2011 caused by Klebsiella species were retrospectively reviewed. The demographic profile, risk factors along with clinical features and management of sepsis were reviewed. Results: Twenty three out of 37 neonatal blood cultures grew Klebsiella species. Thirty one were K. pneumoniae and six K. oxytoca. Seventeen of the 31 (55%) K. pneumoniae isolates were multidrug resistant and extended spectrum beta lactamase producers. Eighteen of 23 (78%) neonates with Klebsiella sepsis died. After extensive cleaning methods and identifying an intermittently leaking roof in one of the nurseries below a vescicovaginal fistula room of gynecological ward above, the infection outbreak was finally controlled. Conclusions: Infections with extended spectrum beta lactamase producing Klebsiella spp. are a threat in neonatal units because of limited treatment options for these multidrug resistant organisms. Identification of the source and control of the outbreak can be a challenge. Plain Language Summary: The study was done to review an outbreak caused by Klebsiella species, to identify the source of the infections along with infection control measures for eradication and prevention of these infections in neonate unit. Identification of the source and eradication of the outbreak of Klebsiella species can be a challenge. Hand washing remains one of the most important methods to prevent cross infections and nosocomial infections. DOI: http://dx.doi.org/10.3126/jpahs.v1i1.13011 Journal of Patan Academy of Health Sciences. 2014 Jun;1(1):20-25